2021
DOI: 10.1007/s00344-021-10437-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Potential Gene Modules Associated with Cold Tolerance in Sugarcane (Saccharum officinarum L.)

Abstract: Sugarcane is an important crop worldwide, and most sugar is derived directly from sugarcane. Due to its thermophilic nature, the yield of sugarcane is largely influenced by extreme climate conditions, especially cold stress. Therefore, the development of sugarcane with improved cold tolerance is an important goal. However, little is known about the multiple mechanisms underlying cold acclimation at the bud stage in sugarcane. In this study, we emphasized that sensitivity to cold stress was higher for the sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The contents of soluble sugar and starch are often related to stress responses in plants [38,39]. The accumulation of soluble sugar may be at least partially triggered by the degradation of polysaccharides [40]; thereby, starch metabolism is thought to be closely related to tolerance against stresses [41]. The high content of starch and the low content of soluble sugar represent a high capacity for stress resistance [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…The contents of soluble sugar and starch are often related to stress responses in plants [38,39]. The accumulation of soluble sugar may be at least partially triggered by the degradation of polysaccharides [40]; thereby, starch metabolism is thought to be closely related to tolerance against stresses [41]. The high content of starch and the low content of soluble sugar represent a high capacity for stress resistance [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2013) found that CDPKs play an important role under low temperature stress in tea (Camellia sinensis). Potential genes related to cold tolerance in sugarcane (Saccharum officinarum) have also been investigated, and the genes related to the regulation of membrane system stability were found to be the determinants of cold tolerance differences, while the key genes that encode protein kinase activity, starch metabolism, and calcium signaling were associated with cold tolerance (Huang et al 2021).…”
Section: Introductionmentioning
confidence: 99%